Crisis leadership and strategic decisions in Swedish maternity care during the COVID-19 pandemic: A deductive analysis from the COPE staff project - Emelie Stotzer; Sofie Graner; Verena Sengpiel; Anna Wessberg; Magnus Akerstrom; Karolina Linden (PLoS ONE, 2026)
Background Healthcare managers played a crucial role during the COVID-19 pandemic, tasked with organizing care for a new medical condition, implementing restrictions to reduce infection spread, and handling unprecedented staff shortage while maintaining operability and ensuring a sustainable working environment for employees. The aim of this study was to generate knowledge about Swedish maternity care managers’ decision-making, by exploring their crisis management to cope and to mitigate the pandemic’s effects in working units. Methods Semi-structured interviews were conducted with 18 managers from various organizational levels at different Swedish maternity care units during the third wave of the pandemic (March – June 2021). A deductive qualitative content analysis informed by the Consolidated Framework for Implementation Research (CFIR), was performed. Results The pandemic compelled managers to employ innovation, reorganization and altered working routines to address external and internal demands. Many decisions were made rapidly, often with limited information and without sufficient time for thorough consideration. Peer support and effective communication were identified as essential for coping with the situation. Managers worked long hours and expressed both challenges in their decision-making and pride in their ability to fulfill their roles. Transparency in the decision-making process, along with continuous reflection and evaluation, were viewed as successful crisis management tools for enhancing workplace sense-making and helping employees maintain motivation. Conclusions Throughout the pandemic, managers had to develop their own methods for making and implementing decisions, aimed at ensuring patient and employee safety and well-being, often without organizational guidance on leading in crisis. It is essential to share knowledge about effective regulatory strategies to mitigate crisis impacts and to incorporate these strategies into crisis management frameworks to strengthen preparedness for future emergencies.